2021
DOI: 10.1111/ffe.13599
|View full text |Cite
|
Sign up to set email alerts
|

Crack evolution law and failure mode of red sandstone under fatigue–creep interaction

Abstract: To explore the fracture characteristics of rock under the interaction of fatigue load and creep load, fatigue–creep interactive loading experiments were performed on red sandstone with prefabricated cracks. The crack evolution process and failure mode were analyzed using acoustic emission technology and digital image correlation. The results showed that crack growth mainly occurred in the fatigue loading stage; the crack evolution of the sample could be divided into three stages: nucleation and initiation ( SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…The failure modes of the rock mass under the interaction of fatigue-creep are all tensile-shear composite failures. At the same time, as the CSL increases, the surface of the sample can produce greater deformation before failure, the brittleness at failure is weakened, and the failure mode gradually changes from brittleness to ductility, which is consistent with the experimental phenomenon of Shi et al 30 and Wang et al 32…”
Section: Crack Evolution Process Analysissupporting
confidence: 85%
See 1 more Smart Citation
“…The failure modes of the rock mass under the interaction of fatigue-creep are all tensile-shear composite failures. At the same time, as the CSL increases, the surface of the sample can produce greater deformation before failure, the brittleness at failure is weakened, and the failure mode gradually changes from brittleness to ductility, which is consistent with the experimental phenomenon of Shi et al 30 and Wang et al 32…”
Section: Crack Evolution Process Analysissupporting
confidence: 85%
“…In terms of fatigue-creep interaction, affected by the heterogeneity and anisotropy of rocks, the existing research mainly focuses on isotropic materials such as metals and asphalt, and there are few related studies on brittle materials such as rocks. 31,32 However, in practical engineering applications, deep engineering rock masses are often under fatigue-creep interaction. Therefore, a series of fatigue-creep tests with different cyclic stress levels (CSL) were carried out on jointed sandstone samples.…”
Section: Introductionmentioning
confidence: 99%
“…To sum up, comparing the failure mode of specimens under high and low stress, it is found that the failure mode is continuously changed from single failure to mixed failure 50 . This indicates that the input of high cyclic stress energy moves particles to become disordered and the specimen is more likely to be destroyed macroscopically.…”
Section: Numerical Simulation Based On Pfc2dmentioning
confidence: 98%
“…To sum up, comparing the failure mode of specimens under high and low stress, it is found that the failure mode is continuously changed from single failure to mixed failure. 50 This indicates that the input of high cyclic stress energy moves particles to become disordered and the specimen is more likely to be destroyed macroscopically. From the change of failure mode with different dip angles, the change of failure mode becomes smaller with the increase of cyclic stress limit with the increase of joint inclination angle.…”
Section: Microstructural Fracture Characteristicsmentioning
confidence: 99%
“…Under the action of external force, there exists the acoustic emission (AE) phenomenon because of the rapid release of local energy and the material’s emissions of transient elastic waves from the inside [ 52 ]. To implement AE monitoring during the particle flow loading process, Zhou Y et al [ 53 , 54 ] and Cai et al [ 55 ] compiled an AE moment tensor operation function into FISH language.…”
Section: Particle Flow Analysis Of Strength Parameter Evolutionmentioning
confidence: 99%